The Impact of Family Friendly Policies in Spain and their Use throughout the Business Cycle - Sara de la Rica; Lucía Gorjón (Institute for the Study of Labor (IZA), 2015)
The aim of this paper is to evaluate various aspects of a family friendly law (Act 39/99) approved in Spain in 1999, which grants parents the right to reduce their work-time schedule for childcare issues. Moreover, those who resort to that law enjoy higher protection against dismissal than other workers, which may encourage workers to use the law as a form of job protection, particularly in recession periods. We first test the direct impact of the law, i.e. whether its passing increased the use of work-time reduction for childcare issues. We find that the use of such measures did indeed increase by around 18%. Second, we test whether the passing of the law led to strategic behavior from employers, in the sense of restricting indefinite contracts to potential users of the law to limit the use of work-time reduction. We find that this is indeed the case. Finally, we test whether this law was resorted to more or less in the recent downturn than in the previous economic upturn. We find that its use decreased by around 13% in the recent downturn, which is not consistent with the view that workers would use the law more intensively during recessions for job protection reasons.
Keywords: C23; J16; J18; J62; 330; policy evaluation; family friendly policies; difference-in-difference; business cycle